Pengaruh Substitusi Abu Ampas Kopi pada Kinerja Beton untuk Mendukung Konstruksi Berkelanjutan - Alwan Kusuma Darmawan; Athaya Zhafirah (Jurnal Konstruksi, 2026)
Coffee grounds are food industry waste produced from processing coffee beans. As with other food industry waste, coffee grounds waste has the potential to be utilized as a partial cement substitution material that is pozzolanic in nature containing silica. The purpose of this study was to determine the compressive strength and tensile strength of concrete containing coffee grounds ash with a composition of 2.5%, 5%, and 7.5% by weight of cement, which was carried out at the age of 28 days. The test specimens were in the form of cylinders with dimensions of 30 cm x 15 cm as many as 24 specimens. The planned concrete quality is 20 MPa (200 Kg/cm²). The average result of the normal concrete compressive strength test was 25.83 MPa, the compressive strength value of concrete using coffee grounds ash with a percentage of 2.5% was 27.02 MPa, a percentage of 5% was 26.18 MPa, and a percentage of 7.5% was 20.56 MPa. The average split tensile strength test result for normal concrete was 2.82 MPa, 2.5% percentage was 2.93 MPa, 5% percentage was 2.72 MPa, and 7.5% percentage was 1.94 MPa.